2019
DOI: 10.1021/acschembio.9b00427
|View full text |Cite
|
Sign up to set email alerts
|

L,D-Transpeptidase Specific Probe Reveals Spatial Activity of Peptidoglycan Cross-Linking

Abstract: Peptidoglycan (PG) is a cross-linked, meshlike scaffold endowed with the strength to withstand the internal pressure of bacteria. Bacteria are known to heavily remodel their peptidoglycan stem peptides, yet little is known about the physiological impact of these chemical variations on peptidoglycan cross-linking. Furthermore, there are limited tools to study these structural variations, which can also have important implications on cell wall integrity and host immunity. Cross-linking of peptide chains within P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(105 citation statements)
references
References 85 publications
(159 reference statements)
6
97
0
Order By: Relevance
“…A wide range of single D-amino acid PG probes have been developed to elucidate fundamental steps in bacterial cell wall biology. 13,[22][23][24][25][26][27][28][29][30][31][32] We also included oxidized D-cystine (2) and D-cysteine amidated in the C-terminus (3) in an attempt to maximize PG tagging. 26,30 Cell treatment with the dipeptide D-Cys-D-Ala (4) was expected to result in the incorporation of D-cysteine at the 4 th position of the stem peptide.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of single D-amino acid PG probes have been developed to elucidate fundamental steps in bacterial cell wall biology. 13,[22][23][24][25][26][27][28][29][30][31][32] We also included oxidized D-cystine (2) and D-cysteine amidated in the C-terminus (3) in an attempt to maximize PG tagging. 26,30 Cell treatment with the dipeptide D-Cys-D-Ala (4) was expected to result in the incorporation of D-cysteine at the 4 th position of the stem peptide.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, cysteine was placed at the N-terminus of a tetrapeptide synthetic analog (5) of the PG stem peptide. We 32,35 , and others [36][37][38][39] , recently showed that structural analogs of PG stem peptides can be crosslinked into the growing PG scaffold of live cells. We proceeded to investigate the role of surface biopolymers on PG accessibility.…”
Section: Resultsmentioning
confidence: 99%
“…I would like to speculate on a putative role of l , d ‐transpeptidases to restrain active growth. These enzymes catalyze the formation of cross‐links between amino acids in third position of adjacent stem peptides, l , d ‐(3‐3) bridges of structure m‐ Dap‐ m‐ Dap (Pidgeon et al, ). Unlike the d , d ‐(4‐3) bridge catalyzed by PBPs, the l , d ‐(3‐3) bridge does not depend on an intact pentapeptide side chain and, as consequence, can be formed in structured mature PG (Figure a).…”
Section: Pg Structural Variations and The Control Of Intracellular Grmentioning
confidence: 99%
“…Because bacteria can recycle more than d ‐Ala, dipeptide reporters have also been developed to monitor the de novo biosynthesis and turnover of peptidoglycan (Figure C) . In addition, dipeptide reporters have also been employed to monitor l,d ‐transpeptidase‐mediated peptidoglycan crosslinking as well as photo‐crosslinking of lipid II‐binding proteins (Figure D) …”
Section: Chemical Reporters For Microbiologymentioning
confidence: 99%